Designing and applying an eco-friendly sink technology for enhanced water management efficiency in household environments - Gapurov A. K.; Hudayberdiyev Ya. H.; Begmatov I. A.; Mamataliev A. B.; Botirov Sh. Ch.; Yulshiev D. G.; Hayitova M. S. (E3S Web of Conferences)
This paper presents a pioneering study on the development and implementation of a sustainable, innovative Eco-sink technology designed to improve water management efficiency in domestic settings. Developed by the authors, the Eco-sink system addresses the widespread issue of inefficient water use in modern homes by integrating a mechanical lever and distributor that regulate water flow and channel it into a reservoir for reuse. The primary objectives of this project are to pursue sustainable solutions, promote climate change resilience and adaptation, engage private sector stakeholders, and raise environmental awareness. A multi-faceted research methodology was employed, including surveys, comparative data analysis, engineering and design assessments, biochemical water evaluations, and experimental implementation. The initiative aims to achieve improved water consumption efficiency, greater adoption of water-conservation systems, the development of innovative water management models and tools, and potential financial benefits. The introduction of Eco-sink technology is expected to make a substantial contribution to sustainable household water management, reduce environmental impacts, and foster a more environmentally conscious society. This study marks a significant step toward addressing water management challenges in residential areas and offers a practical solution aligned with broader environmental sustainability goals.